THE SCHOOL-LEVEL FACTORS OF EFFECTIVE SCHOOLING - Dovhopolova, Hanna Hennadiivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. The 21st century began with a massive effort to improve Ukrainian secondary school and pupils’ academic achievements. Schools can have a tremendous impact on students’ achievements if they consider a few factors that can actually support the position that schools do make a difference. In particular, the factors of school level need to be studied and systematized, because educational institutions have the opportunity to influence them, whereas the factors of regional or state level are not their prerogative. The purpose of the article is to identify the most significant school-level factors that influence successful learning of students. Results. In spite of the differences between the lists a deeper analysis can prove that most researchers address the same five basic factors. Most of them address setting academic goals for all students that do not underestimate their potential and that provide feedback as to progress. Therefore, all these factors can be organized into these five school-level factors: 1. Guaranteed and viable curriculum: opportunity to learn and time by R. Marzano, content coverage and time by J. Scheerens, concentration on teaching and learning by P. Sammons, focus on central learning skills by D. Levine, emphasis on basic skill acquisition by R. Edmonds. 2. Challenging goals and effective feedback: monitoring and pressure to achieve by R. Marzano and J. Scheerens, high expectations and monitoring progress by P. Sammons, high expectations and requirements and appropriate monitoring by D. Levine, high expectations for student success and frequent monitoring of student progress by R. Edmonds. 3. Parent and community involvement: parental involvement by R. Marzano and J. Scheerens, home-school partnership by P. Sammons, salient parental involvement by D. Levine. 4. Safe and orderly environment: school climate by R. Marzano and J. Scheerens, a learning environment, positive reinforcement and pupil rights and expectations by P. Sammons, productive climate and culture by D. Levine, safe and orderly atmosphere conducive to learning by R. Edmonds. 5. Collegiality and professionalism: leadership and cooperation by R. Marzano and J. Scheeren, professional leadership, shared vision and goals and a learning organization by P. Sammons, strong leadership and practice-oriented staff development by D. Levine, strong administrative leadership by R. Edmonds. These factors are listed in rank order in terms of their impact on students’ achievement, although it does not mean that the factors with lower rank are not critical to the effective running of a school. Those factors positively impact students’ achievement up to a certain point only. Such relationships are typically referred to as nonlinear. Conclusion. Comparative analysis of the researches in the field of theory of education end educational management allowed defining the most significant school-level factors that influence successful learning of students. These factors are: guaranteed and viable curriculum, collegiality and professionalism, parent and community involvement, safe and orderly environment, challenging goals and effective feedback.